Canva Application Training to Increase Cake Business Productivity in Teluk Jambe Timur, Karawang: Pelatihan Aplikasi Canva untuk Meningkatkan Produktifitas Usaha Kue di Teluk Jambe Timur Karawang - Nita Hidayati; Hanifah, Hanifah; Betha Nurina Sari; Marsah Rahmawati Utami; An Nisaa Mutiara Salsabila; Nadia Meisya Nur Faedah; Tiara Destia Fitri; Widya Tri Indarti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Teluk Jambe Timur is a village in Karawang Regency, West Java which has a very strategic location. This is a business opportunity for several groups of housewives. The main problem faced by partners is that the marketing process is only based on orders and needs of existing customers, so their business is underdeveloped. The output of the activity is improving skills in information technology such as photo editing using Canva which is needed to beautify the appearance of promotional media. The method used is a training method for optimizing cake production as well as digital marketing training which will be accompanied by the implementing team and students. The essence of the training activity is to generate lots of ideas and then produce new designs that are unique to each product by developing product ideas. The end of the activity resulted in fluency, flexibility, originality and elaborative innovation regarding logos, packaging designs, more attractive promotional media covers which progressively increased before using the Canva application and after attending training of at least 85% to 95%.